Thermophysical properties and thermal characteristics of phase change emulsion for thermal energy storage media. (15th December 2016) - Kawanami, Tsuyoshi; Togashi, Kenichi; Fumoto, Koji; Hirano, Shigeki; Zhang, Peng; Shirai, Katsuaki; Hirasawa, Shigeki
Abstract: A great deal of attention has been paid to energy saving devices in place of conventional air-cooled and water-cooled devices. The thermal energy storage system that uses the latent heat of a PCM (phase change material) for air-conditioning or heating has recently become popular because it does not require high electric power and it saves energy. An emulsion dispersed nano-size particles of phase change material is produced. We discuss with the thermophysical properties, the stability of emulsion, and the heat transport characteristics as a thermal functional fluid. The testing emulsion, which has nano-size particles as the discrete phase, is produced with ad -phase emulsification method. The diameter of discrete phase in the emulsion is measured for evaluation of the long-term stability of emulsion. In addition, the DSC (differential scanning calorimetry) curve of emulsion is determined. Thermophysical properties such as viscosity and thermal conductivity of emulsions were studied in this work, and was compared with that of the base fluid. The results reveal that the emulsion with thed -phase emulsification method has the superior stability. From the differential thermal analysis, the DSC curve of present emulsion indicates a discontinuous change at the phase change temperature of phase change material due to its latent heat. Highlights: A nanoemulsion containing nano-size PCM displays a characteristic thermal tendency. The emulsion with a D-phase emulsification method shows a superior stability. The viscosity of nanoemulsion indicates about twice higher value of water. A large change in thermal conductivity is measured near the melting point.